A framework for analysis of the supplier selection in green supply chain - Tundys, Blanka; Rzeczycki, Andrzej; Fernando, Yudi (Inderscience Enterprises Ltd., 2019)
supply chain. To achieve this purpose, specific objectives were taken to consideration: 1) an indication of the basis for the analysis of supplier selection in green supply chain; 2) identify of the gaps that exist in this respect, in the literature; 3) the identification of the criteria catalogue for the supplier selection with the particular emphasis on the needs of green supply chain; 4) develop a model to assess the green supply chain, taking into account the sustainable aspects; 5) using AHP method to the investigation and analysis of the meaning of the selected criteria, on the example of companies operating in the Polish economy; 6) indication which of them are the most important and which of them did not play an important role in the selection process of the suppliers.